Dual oocyte retrieval and embryo transfer in the same cycle for women with premature ovarian insufficiency. Issue 1 (15th February 2019) - Hatirnaz, Safak; Ata, Baris; Hatırnaz, Ebru; Basbug, Alper; Tannus, Samer
Abstract: Objective: To compare dual oocyte retrieval with minimal ovarian stimulation and embryo transfer in the same menstrual cycle versus conventional ovarian stimulation among women with premature ovarian insufficiency (POI). Methods: A retrospective study of 51 women with POI attending a reproductive center in Turkey between 2013 and 2015. Women with an ovarian follicle of 12 mm or larger early in the follicular phase who underwent oocyte retrieval followed by an immediate cycle of ovarian stimulation (group 1, n=14) were compared with those who received conventional ovarian stimulation (group 2, n=37). Both groups underwent subsequent ovarian stimulation cycles to obtain optimally two embryos for transfer. Results: The groups had similar baseline parameters. Serum estradiol was higher in group 1 ( P <0.001); total number of oocyte retrievals was higher in group 2 ( P <0.001); and total number of oocytes retrieved was similar ( P =0.192). Group 1 had more higher‐quality embryos ( P =0.031). There was a non‐significant trend toward higher live birth rates in the dual trigger group (28% vs 8%, P =0.08). Conclusion: Rescuing growing follicles early in the follicular phase combined with subsequent ovarian stimulation and embryo transfer in the same cycle resulted in fewer oocyte retrieval cycles and might potentially improve reproductive outcomes. Abstract : For women with premature ovarian insufficiency, rescuing spontaneously growing ovarian follicles early in the follicular phase before commencing ovarian stimulation might improve reproductive outcomes.